Fibroblast Growth Factor 21 Analogs for Treating Metabolic Disorders - Zhang, Jun; Li, Yang (Frontiers in Endocrinology, 2015)
Fibroblast growth factor (FGF) 21 is a member of the endocrine FGF subfamily. FGF21 expression is induced under different disease conditions, such as type 2 diabetes, obesity, chronic kidney diseases, and cardiovascular diseases, and it has a broad spectrum of functions in regulating various metabolic parameters. Many different approaches have been pursued targeting FGF21 and its receptors to develop therapeutics for treating type 2 diabetes and other aspects of metabolic conditions. In this article, we summarize some of these key approaches and highlight the potential challenges in the development of these agents.